2007
DOI: 10.1152/japplphysiol.01425.2006
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia and cystic fibrosis alter respiratory fluid glucose concentrations estimated by breath condensate analysis

Abstract: In animals, glucose concentrations are 3-20 times lower in lung lining fluid than in plasma. In humans, glucose concentrations are normally low (<1 mmol/l) in nasal and bronchial fluid, but they are elevated by inflammation or hyperglycemia. Furthermore, elevated bronchial glucose is associated with increased respiratory infection in intensive care patients. Our aims were to estimate normal glucose concentrations in fluid from distal human lung sampled noninvasively and to determine effects of hyperglycemia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
156
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 163 publications
(170 citation statements)
references
References 27 publications
11
156
1
1
Order By: Relevance
“…Therefore, the in vitro data presented in this study support the notion that the human airway is relatively leaky to glucose. They also support our previous observations in vivo that glucose rapidly diffuses across the epithelium into ASL when blood glucose is raised in human subjects [3,40].…”
Section: Paracellular Diffusion Of L-glucosesupporting
confidence: 91%
See 4 more Smart Citations
“…Therefore, the in vitro data presented in this study support the notion that the human airway is relatively leaky to glucose. They also support our previous observations in vivo that glucose rapidly diffuses across the epithelium into ASL when blood glucose is raised in human subjects [3,40].…”
Section: Paracellular Diffusion Of L-glucosesupporting
confidence: 91%
“…We have previously shown that glucose concentrations in normal ASL are approximately 12.5 times lower than blood glucose concentrations [3]. Our human observations are similar to those in sheep and rat lungs where glucose concentrations were three times to 20 times lower in ASL than in blood [5,33].…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations